Comparative analysis of LTE backbone transport techniques for efficient broadband penetration in a heterogeneous network morphology - Ajibo Augustine; Chinaeke-Ogbuka Ifeanyi; Udechukwu Felix (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In the bid to bring about a solution to the nagging problem associated with the provision of ubiquitous broadband access, Next Generation Network (NGN) popularly referred to as Long Term Evolution (LTE) network with appropriate network integration technique is recommended as solution. Currently, Internet Protocol/Multi-Protocol Label Switching (IP/MPLS) is the transport technique in LTE backbone infrastructure. This technique, however, suffers significantly in the event of failure of IP path resulting in delay and packet loss budgets across the network.The resultant effect is degradation in users’ quality of service (QoS) experience with real-time services.  A competitive alternative is the Internet Protocol /Asynchronous Transfer Mode (IP/ATM). This transport technique provides great dynamism in the allocation of bandwidth and supports varying requests of multimedia connections with diverse QoS requirements. This paper, therefore, seeks to evaluate the performance of these two transport techniques in a bid to establish the extent to which the latter technique ameliorates the aforementioned challenges suffered by the previous technique. Results from the simulation show that the IP/ATM transport scheme is superior to the IP/MPLS scheme in terms of average bandwidth utilization, mean traffic drop and mean traffic delay in the ratio of 9.8, 8.7 and 1.0% respectively.